The Political Dynamics on Development Process of Human Rights Cities: Lessons from South Korea and Indonesia - Zico Mulia (Indonesian Journal of Political Studies, 2021)
There has not been a comparative study on the human rights cities in South Korea and Indonesia. Therefore, this paper conduct a comparative study of the dynamics within the development process of the human rights city in Gwangju and Wonosobo. This study explains how both cities flourished into Human Rights Cities using agenda-building theory. Moreover, this research elucidates the main actors and their respective roles in the development of both Human Rights Cities. Employing qualitative methods of data collection and analysis, this study found similarities and differences between the development processes of both Human Rights Cities. This article found that civil society organizations’ efforts were influential in the initiation stage in Gwangju. Meanwhile, in the case of Wonosobo, the concept of brandishing itself as a Human Rights City came from the Mayor. As a result, the top-down agenda-building process in Wonosobo took place faster than the development of the bottom-up human rights city of Gwangju.